The future role of radiologists in the artificial intelligence-driven hospital: letter to the editor - Sedaghat, Sam (Annals of biomedical engineering, 2024)
Increasing population and healthcare costs make changes in the healthcare system necessary. This article deals with ChatGPT’s perspective on the future role of radiologists in the AI-driven hospital. This perspective will be augmented by further considerations by the author. AI-based imaging technologies and chatbots like ChatGPT can help improve radiologists’ performance and workflow in the future AI-driven hospital. Although basic radiological examinations could be delivered without needing a radiologist, sophisticated imaging procedures will still need the expert opinion of a radiologist.
Gesehen am 10.10.2024